The «vital energy» and the return to the community - Santisteban-D., Nathalie (2011)
This article focuses on the relationship between ritual and migration in the Andean region of southern Peru. Among the highland shepherds of Santa Bárbara and Q’ero, the rituals of Carnival are considered to be the most important part of their vision of the world. On the one hand, the shepherds ask their divinities to protect and increase the number of animals, and on the other, they try to maintain and renew the reciprocity-dependency” relationship with their divinities (Apu and Pachamama). In order to achieve this, the shepherds, as much as the migrants, perform rituals and give offerings to the Apu and Pachamama. The purpose of these ritual practices is to try to achieve “buen vivir” (good living) for the rest of the year.